Value Chain Development for Efficient Agricultural Marketing - Hegde, Narayan G. (Indian Farming, 2015)
Value chain is a platform where all the stakeholders associated with a particular crop or commodity, share a common platform and interact among each other with a goal of optimising the production and value addition. These are the intermediaries between the farmers and consumers. They include scientists, extension experts, development agencies and farmers’ organisations, input producers and distributors, financial institutions and insurance agencies, traders, warehouse owners, transporters, processing establishments and marketing organisations. Local farmers’ cooperatives, dedicated civil society organisations or Producer Companies can take the lead in coordinating the value chain platform.